' ... nice to get some alone time': children's spatial negotiation of alone time needs in the family home - Costa Santos, Sandra; Parnell, Rosie; Abo Kanon, Husam; Pattinson, Emily; Pitsikali, Alkistis; Sarhan, Heba (Children's geographies, 2024)
This article exposes the spatial dimensions that children seek to support their alone time needs in the family home, based on empirical data from the At Home with Children research project. Domestic ideals problematise child alone time at home as a threat to family togetherness. In turn, housing foregrounds this idea through the move towards open-plan living and overcrowding policy's indifference to children's 'alone space' needs. This article offers new thinking by exploring the perspectives of children and teenagers on the everyday spatial negotiation of their alone time needs while at home with family during COVID-19 lockdown. Findings from semi-structured interviews with 45 families living across England and Scotland, UK, reveal that both children and teenagers seek spaces for alone time to enable four core experiences: privacy, agency, ownership, and restoration. Here, associated dimensions of space are identified by children and teenagers, contributing new understandings to children's domestic geographies and showing the relevance of space for alone time, to children's well-being, fundamentally challenging adult-centred constructions of family togetherness. The article's focus on the voiced needs of children sets a new agenda for the housing standards, with major policy implications for measures of occupation density, which can enable children's well-being.